INFLUENCE OF BODY HEIGHT, BODY WEIGHT AND THE AGE ON THE RESULTS ACHIEVED BY MAN-MARATHONERS IN A MARATHON RACE - Naser Rašiti Naser; Vlora Ajvazi; Adem Nura; Halim Hajredini (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research is conducted on a sample of 100 successful man marathoners who has taken part in ten of the most popular marathon races. The sample of entities includes ten of the best placed marathoners in each race held during the year 2008. The aim of the research is to assess the influence of the body height, weight and the age of the marathoners on the final result in the race. The collected data is processed by the basic descriptive parameters. The entities have the average weight of 56.94 kg, with the average height of 168.98 cm, at the average age of 29.75, with the achieved average result of 2:13.23 hours in the race. In the intercorrelation matrix only one significant coefficient of correlation is obtained (p<0.001) between the body height and body weight. By the regressive analysis the influence of the predictory variables (height, weight and age) on the criteria variable - sig. =0, 21 (the result of the marathon) is not confirmed, which provides only 15% (RO²=.302) of analysis in the common ground of variability. The rest of 91% in analysing the total variability of the criteria variable can be ascribed to some other anthropologic characteristics, and mainly to the functional characteristics of anaerobic type.